Models of parent-teacher cooperation to enhance religious values and moral character In young children - Siti Maisaroh; Happy Susanto; Bambang Harmanto (ISTAWA, 2025)
The initial phase or foundation of child development begins in early childhood. This development phase will determine the next phases. Development and learning in PAUD are integrated into daily habits. Instilling religious values and morals is very important in shaping children's character so that good cooperation between parents and teachers is needed, namely by establishing coordination, communication and collaboration. The author conducted this study with the aim of 1) To find out the planning of cooperation between parents and teachers as an effort to improve religious values and morals in early childhood at RA Muslimat NU 094 Sooko District, 2) To find out the implementation of the cooperation and 3) To find out the results of the evaluation of cooperation programs or activities that can improve religious values and morals. The implementation of cooperation in reality is certainly not as easy as planned, there are challenges, obstacles and barriers. Instilling religious values and morals at RA Muslimat NU 094 Sooko District has been going well, but the consistency and sustainability of programs that support religious values and morals need to be improved. Based on this, the author conducted a study using a qualitative method with a descriptive approach. The process of planning, implementation and evaluation, the researcher conducted observations, interviews and documented the activities of parental cooperation to improve religious values and morals at RA Muslimat NU 094 Sooko District and concluded that the planning of programs or activities had been carried out at the beginning of the school year and in its implementation it was integrated with learning and children's daily activities so that in instilling and strengthening religious values and morals, intense synergy was needed between the school and parents. The implementation of the evaluation must consider the perspective of all school residents by taking policies that are biased and oriented towards children's learning needs. Fase awal atau fondasi perkembangan anak dimulai sejak anak usia dini. Pada fase perkembangan inilah yang akan menjadi penentu pada fase-fase berikutnya. Perkembangan dan pembelajaran di PAUD terintegrasi ke dalam pembiasaan sehari-hari. Penanaman nilai agama dan budi pekerti menjadi hal yang sangat penting dalam membentuk karakter anak sehingga kerjasama yang baik antara orang tua dan guru sangat diperlukan yaitu dengan menjalin koordinasi, komunikasi dan kolaborasi. Penulis melaksanakan penelitian ini dengan tujuan yaitu 1) Untuk mengetahui perencanaan kerjasama orangtua dan guru sebagai upaya peningkatan nilai agama dan budi pekerti pada anak usia dini di RA Muslimat NU 094 Kecamatan Sooko, 2) Untuk mengetahui pelaksanaan atas kerjasama tersebut dan 3) Untuk mengetahui hasil evaluasi program atau kegiatan kerjasama yang dapat meningkatkan nilai agama dan budi pekerti. Pelaksanaan kerjasama pada kenyataannya tentu tidak semudah seperti yang direncanakan, ada tantangan kendala maupun hambatan. Penanaman nilai agama dan budi pekerti di RA Muslimat NU 094 Kecamatan Sooko sudah berjalan dengan baik, akan tetapi konsistensi serta keberlanjutan atas program yang mendukung nilai agama dan budi pekerti perlu ditingkatkan. Berdasarkan hal tersebut penulis melaksanakan penelitian menggunakan metode kualitatif dengan pendekatan deskriptif . Proses perencanaan, pelaksanaan serta evaluasi, peneliti melaksanakan observasi, wawancara serta mendokumentasikan kegiatan kerjasama orang tua untuk meningkatkan nilai agama dan budi pekerti di RA Muslimat NU 094 Kecamatan Sooko serta menghasilkan kesimpulan bahwa perencanaan program atau kegiatan telah dilaksanakan di awal tahun ajaran dan pada pelaksanaannya terintegrasi dengan pembelajaran serta kegiatan sehari-hari anak sehingga dalam menanamkan serta menguatkan nilai agama dan budi pekerti dibutuhkan sinergi intens antara pihak sekolah dan orang tua. Pelaksanaan evaluasi harus memperhatikan sudut pandang seluruh warga sekolah dengan mengambil kebijakan yang berpihak dan berorientasi pada kebutuhan belajar anak.